Relationship between self-care and depression and anxiety symptoms in individuals undergoing hemodialysis - Loren Caroline Bettoni; Ana Carolina Ottaviani; Fabiana de Souza Orlandi (Rev Rene)
Objective: to evaluating the ability for self-care and its relationship with depression and anxiety symptoms in hemodialysis patients. Methods: a correlational, cross-sectional study conducted with 100 participants. The following instruments were used: Appraisal of Self Care Agency Scale – Revised (ASAS-R), which indicates the ability of patients to self-care, and the Hospital Anxiety and Depression Scale, which evaluates the presence or absence of depression and anxiety symptoms. Results: the participants had a mean score of 60.64 (±8.24) on the Appraisal of Self Care Agency Scale - Revised, indicating a good level of self-care agency. A negative correlation of moderate magnitude was found between the ability to self-care and symptoms of anxiety (r=-0.328) and depression (r=-0.387). Conclusion: individuals undergoing hemodialysis treatment presented good self-care agency and those with depression and/or anxiety symptoms showed less ability to self-care.